C1-esterase inhibitor treatment: preclinical safety aspects on the potential prothrombotic risk - Schürmann, Daniel; Herzog, Eva; Raquet, Elmar; Nolte, Marc W.; May, Frauke; Müller-Cohrs, Jochen; Björkqvist, Jenny; Dickneite, Gerhard; Pragst, Ingo (Thrombosis and Haemostasis, 2014)
Human plasma-derived C1-esterase inhibitor (C1–INH) is an efficacious and safe treatment for hereditary angioedema. However, thrombotic events in subjects treated with C1–INH at recommended or offlabel, high doses have been reported. In this study, we addressed the potential prothrombotic risk of C1–INH treatment in high doses using a non-clinical rabbit model. Following intravenous infusion of C1–INH to rabbits at doses up to 800 IU/kg, the exposure and the pharmacodynamic efficacy of C1–INH in rabbits were confirmed by activity measurements of C1-esterase, and coagulation factors XIa and XIIa, respectively. Potential prothrombotic effects were assessed following induction of venous and arterial thrombosis using in vivo models of venous and arterial stasis, complemented by various in vitro assays of coagulation markers. Administration of C1–INH at doses up to 800 IU/ kg did not potentiate thrombus formation during venous stasis. In contrast, inhibition of arterial occlusion was observed upon C1–INH administration when compared with isotonic saline treatment, indicating antithrombotic rather than prothrombotic activity of high dose C1–INH treatment in vivo. This was further confirmed in vitro by decreased thrombin generation, increased activated partial thromboplastin time, clotting time and clot formation time, and inhibition of platelet aggregation. No relevant changes in fibrinolysis or in the levels of thrombin-antithrombin complexes, and prothrombin fragment 1+2 were observed upon high dose C1–INH treatment. The data suggest that treatment of healthy rabbits with high doses of C1–INH could potentially inhibit coagulation and thrombus formation rather than induce a prothrombotic risk.
Keywords: Animal model; C1-esterase inhibitor; coagulation; contact activation system; thrombosis